Application of Evidence-Based Nursing Intervention in the Treatment of Advanced Squamous Cell Carcinoma of the Lung by Erlotinib Combined with Tegafur, Gimeracil, and Oteracil Potassium and Its Influence on Quality of Life. (13th December 2021) - Liu, Shan; Huang, Xiaocheng; Wen, Jin; Fu, Fangfang; Wang, Huifen
Abstract : Objective . To explore the application of evidence-based nursing intervention in the treatment of advanced squamous cell carcinoma of the lung by erlotinib combined with tegafur, gimeracil, and oteracil potassium (TS-1) and its influence on quality of life (QOL). Methods . Clinical data of 92 patients with advanced squamous cell carcinoma of the lung treated with erlotinib and TS-1 in our hospital (January 2017–January 2021) were retrospectively analyzed. Forty-six patients receiving conventional nursing were set as the control group (CG), and other 46 patients receiving evidence-based nursing intervention additionally were set as the study group (SG). The clinical observation indexes of the two groups were compared and analyzed. Results . No obvious difference in general data between both groups (P > 0.05 ). According to EORTC QLQ-C30, compared with the CG, the scores of role function, physical function, social function, cognitive function, and emotional function in the SG were remarkably higher (P < 0.05 ). After intervention, scores of VAS of patients were obviously lower than those before intervention (P < 0.05 ), and scores of VAS in the SG after intervention were obviously lower than those in the CG (P < 0.05 ). After intervention, scores of SAS and SDS were lower than those before intervention, and those of the SG were obviously lower than those of the SG (P < 0.05 ). Compared with the CG, incidences of adverse reactions such as diarrhoea, nausea and vomiting, erythra, pressure sores, and leukopenia in the SG were obviously lower (P < 0.05 ). Compared with the CG, "very satisfied" and total satisfaction in the SG were obviously higher (P < 0.05 ). Conclusion . Application of evidence-based nursing intervention in the treatment of advanced squamous cell carcinoma of the lung by erlotinib combined with TS-1 can help patients to relieve pain, improve their psychological state, reduce the incidence of adverse reactions, significantly improve the QOL, and also enhance the satisfaction of clinical nursing.